Pertimbangan Hakim Terhadap Wanprestasi Dalam Perjanjian Hutang Piutang (Studi Putusan Nomor: 38/Pdt.G.S/2024/PN.Tjk) - Hellenia, Shalsabila; Rusli, Tami; Anggalana, Anggalana (SAKOLA: Journal of Sains Cooperative Learning and Law, 2025)
Default is an event or condition, where the debtor does not fulfill his obligation to perform his obligations properly, and the debtor fulfills the elements of wrong for the act. This article discusses the legal consequences of default in a debt agreement in a civil case and also the Judge's Consideration in imposing legal sanctions on the party who commits default. Based on Decision Number : 38 / Pdt.G.S. / 2024 / PN.Tjk. The method used in this study is a normative legal approach with an analysis of court decisions as primary legal material. The results of the study show that the judge considered the validity of the agreement, evidence of default, and the absence of good faith from the defendant. In addition, the judge also considered the principle of proportionality in determining the compensation to be paid. The legal consequences of default in this case are the defendant's obligation to pay material losses and fines in accordance with the provisions of the agreement and civil law. The decision reflects the judge's efforts to uphold the principles of justice, legal certainty, and protection for the injured party.